Globalisation and trust in Europe between 2002 and 2018 - Loesje Verhoeven; Jozef M. M. Ritzen (Research in Globalization, 2023)
Are institutional trust and interpersonal trust threatened by globalisation? For nineteen countries in Europe, using a fixed effects model for a panel data set relating globalisation to several economic and social macro variables, like income inequality and diversity, to average institutional and interpersonal trust derived from responses in European Social Surveys, we do not find any significant relation between the relatively moderate globalisation of the first two decades of the 21st century on average interpersonal and institutional trust. At the same time, occurrences of economic decline in a country are negatively related to institutional trust. GDP has a positive effect on both institutional and interpersonal. Combining the macro factors with the individual traits of respondents using pooled repeated cross-sectional data demonstrate the dominance of personal characteristics in individual levels of trust, with only institutional quality emerging as a macro variable which is significantly and positively related to trust, especially for the Socio-Economic Groups 3 to 7 (of the eight groups distinguished). Those who are born in the country exhibit higher levels of interpersonal trust, in particular in the higher SES groups 4-7, but show significantly lower institutional trust for the SES groups 0-2. Age is negatively related to institutional trust for all SES groups, but positively related to interpersonal trust for SES groups 4-7. These findings appear to imply that those who are concerned with the level of institutional trust in the population as a basic requirement for democracy in Europe should focus on the quality of institutions and not on globalisation.
Keywords: 330; Diversity; Economic decline; Globalisation; Government expenditure; Government intervention; Inequality; Institutional trust; Interpersonal trust